ENHANCING PROFESSIONAL COMPETENCY VALIDATION FOR EDUCATIONAL WORKERS (leveraging international experience for Ukraine) - Terentieva, Nataliia; Levchenko, Yana; Kotova, Anna; Tan, Lipin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The exchange of knowledge and experiences between nations has become imperative for sustainable development and progress today. Ukraine nowadays seeks to enhance the validation process for professional competencies of educational workers. Drawing upon the practical experiences of countries like China, various European nations, the United States, can offer invaluable insights and strategies to optimise Ukraine's educational system. The article aims to present the experience of different countries that by adopting it for education workers` professional competency validation equips Ukraine with a comprehensive toolkit to address the challenges. In particular, the validation of PR China`s (known for its emphasis on rigorous educational standards and competency validation processes), EU`s (diverse educational systems of UR countries offer a rich tapestry of approaches to competency validation), US (accreditation processes and performance-based assessments), Baltic Countries (progressive education policies and commitment to quality assurance) experience, can not only enhances the quality and innovation within Ukraine's educational system but also positions Ukrainian professionals on the global stage. The article as well pays attention not only to benefits that this or that abroad professional validation systems adoption can give Ukraine nowadays, but also makes prognoses as to its practical possibility and possible difficulties.